Biomedical Risk Factors for COVID-19 among People Living with HIV during the First Wave of the Pandemic - Folayan MO; Abeldaño Zuñiga RA; Aly NM; Yousaf MA; Ellakany P; Idigbe IE; Lawal FB; Khalid Z; Lusher J; Virtanen J; El Tantawi M. (United States, 2025)
Objective: We assessed the associations between testing positive for COVID-19 and HIV viral load, and access to and adherence to antiretroviral therapy during the initial phase of the COVID-19 pandemic.
Methods: We conducted a secondary analysis of data, where we extracted complete information for 904 participants self-identifying as HIV positive. The dataset encompassed the dependent variable (testing positive for COVID-19), independent variables (HIV viral load, access to a 90-day supply of antiretroviral drugs, adherence to antiretroviral therapy), and confounding variables (age, sex assigned at birth, living with HIV co-morbidities, and self-reported depression).
Results: Adherence to antiretroviral therapy (AOR: 0.364; 95% CI: 0.231-0.574; p < .001) was significantly association with decreased odds of testing positive for COVID-19. We found no statistically significant associations between HIV viral load or access to a 90-day supply of antiretroviral drugs and testing positive for COVID-19.
Conclusion: The results underscore the necessity for ongoing HIV treatment adherence counseling for individuals with HIV during the COVID-19 pandemic. Further research is warranted to elucidate the paradox wherein adherence to antiretroviral therapy was associated with testing positive for COVID-19, but HIV viral load was not.